What Americans know about politics and why it matters - Delli Carpini, Michael X., 1953-; Keeter, Scott (Yale University Press, 1996)
This book is the most comprehensive analysis ever written about the American public's factual knowledge of politics. Drawing on extensive survey data, including much that is original, two experts in public opinion and political behavior find that many citizens are remarkably well informed about the details of politics, while equally large numbers are nearly ignorant of political facts. And despite dramatic changes in American society and politics, citizens appear no more or less informed today than half a century ago.